The Impact of Sustainability Disclosure And Information Asymmetry on The Cost of Equity: The Moderating Role of Leverage - Senja, Meta (Lembaga Penerbit Fakultas Ekonomi dan Bisns, Universitas Trisakti, 2022)
Sustainability disclosures play a crucial role in reducing the cost of equity by enhancing corporate transparency, yet their impact still needs to be explored in emerging markets like Indonesia. This study aims to bridge this gap by investigating the influence of economic, environmental, and social sustainability disclosures and information asymmetry on the cost of equity, with leverage serving as a moderating factor. Using multiple regression analysis on data from companies listed on the Indonesia Stock Exchange (IDX) between 2014 and 2018, the study reveals that economic sustainability disclosure significantly lowers the cost of equity, while environmental and social disclosures do not show a significant impact. Additionally, information asymmetry is found to increase the cost of equity, aligning with Agency Theory. Leverage, however, does not significantly moderate the relationships between sustainability disclosures and the cost of equity. The findings underscore the importance of economic transparency in reducing capital costs and highlight the need for more robust regulatory frameworks to enhance the effectiveness of environmental and social disclosures.